Student and Teacher Perceptions of First Language Use in Secondary French Immersion Mathematics Classrooms - Culligan, Karla (Alberta Journal of Educational Research, 2015)
This phenomenological study (Creswell, 2003, 2007; van Manen, 1997) explores student and teacher perceptions of first language use in French immersion mathematics classrooms at a large, urban high school in Canada. During individual interviews, participants discussed their perceptions and experiences of French immersion mathematics, language use, and, in particular, first language use. Interview data are analysed through a sociocultural theory lens (e.g., Lantolf, 2000; Swain & Lapkin, 2000), drawing on key notions such as language interdependence and the use of language as a cognitive tool. While first language use in second language classrooms remains controversial, this article contributes to an open discussion on the potential role students’ first language can play in determining effective language and content learning. Cette étude phénoménologique (Creswell, 2003, 2007; van Manen, 1997) porte sur les perceptions des élèves et des enseignants sur l’emploi de la langue première pendant les cours de mathématiques dans un contexte d’immersion française d’une grande école secondaire en milieu urbain au Canada. Pendant les entrevues individuelles, les participants ont discuté de leurs perceptions et leurs expériences relatives aux cours de mathématiques en immersion et à l’emploi de langue, notamment la langue première. Les données d’entrevues ont été analysées dans l’optique de la théorie socioculturelle (p.ex., Lantolf, 2000; Swain & Lapkin, 2000), puisant dans des notions clés telles l’interdépendance des langues et l’emploi de langue comme outil cognitif. Alors que l’emploi de la première langue dans les classes d’immersion est controversé, cet article contribue à une discussion ouverte sur le rôle potentiel que peut jouer la langue première des élèves dans la détermination de l’apprentissage efficace de la langue et du contenu.